2006
DOI: 10.1074/jbc.m513030200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Preferential Recognition of Diaminopimelic Acid-type Peptidoglycan by a Subset of Peptidoglycan Recognition Proteins

Abstract: Drosophila peptidoglycan recognition protein (PGRP)-LCx and -LCa are receptors that preferentially recognize meso-diaminopimelic acid (DAP)-type peptidoglycan (PGN) present in Gram-negative bacteria over lysine-type PGN of Gram-positive bacteria and initiate the IMD signaling pathway, whereas PGRP-LE plays a synergistic role in this process of innate immune defense. How these receptors can distinguish the two types of PGN remains unclear. Here the structure of the PGRP domain of Drosophila PGRP-LE in complex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
134
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 46 publications
8
134
0
Order By: Relevance
“…Crystal structures of PGN fragments bound to human or insect PGRPs (15,16,27,28), including the PGRP-I␤C-GMPP complex, have shown that the fragments adopt a similar overall conformation and interaction mode, with some variations around the saccharide and C terminus of the peptide stem (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystal structures of PGN fragments bound to human or insect PGRPs (15,16,27,28), including the PGRP-I␤C-GMPP complex, have shown that the fragments adopt a similar overall conformation and interaction mode, with some variations around the saccharide and C terminus of the peptide stem (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The PGN-binding site of PGRP-I␤C, whose general topology is maintained in other PGRPs (15,(21)(22)(23)(24)(25)(26)(27)(28), resides in a long cleft whose walls are formed by helix ␣1 and five loops (␤3-␣1, 1␣-␤4, ␤5-␤6, ␤6-␣2, ␤7-␣3) that project above the central ␤-sheet platform ( Fig. 2 A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the third amino acid, L-Lysine is found in the majority of Gram-positive bacteria, whereas meso-diaminopimelic acid (mDAP) is present in Gram-negative bacteria and Gram-positive bacilli (5). Indeed, it has been shown that Lys-type PG is a potent activator of Toll, and DAP-type PG induces primarily the Imd pathway (4,(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Two crystal structures were recently reported: the PGRP domain of Dm-PGRP-LE in complex with tracheal cytotoxin (TCT), a naturally occurring monomer unit of DAP-type PG (32); and the ectodomains of Dm-PGRP-LCa and Dm-PGRP-LCx in complex with TCT (33). These two reports provided the first evidence that protein-protein interactions induced by the monomeric DAP-type PG from Gram-negative bacteria is likely to be essential to activation of the Imd pathway.…”
Section: How Is Lys-type Pg Recognized In Drosophila?mentioning
confidence: 99%